Analysis of Digital Archive Management Using Google Spreadsheets in the Educators and Education Personnel Section of the Education Office - Sugiarto Sugiarto; Supadi Supadi (Universitas Negeri Semarang, 2024)
This study examines the use of Google Spreadsheet as an innovative tool in managing digital archives in the Educators and Education Personnel Section of the Education Office Region I of South Jakarta. The background of this research stems from the increasing complexity of archive management due to technological advancements and the growing need for more efficient and secure archive systems. The use of cloud-based technology like Google Spreadsheet is expected to provide solutions to overcome challenges in managing digital archives, particularly in the processes of planning, maintenance, disposal, and supervision. The objective of this research is to explore the use of Google Spreadsheet in digital archive management and to identify the challenges and solutions that can be implemented to improve the efficiency and security of archive management within the education office. This study employs a qualitative approach with descriptive methods, gathering data through in-depth interviews with informants, direct field observations, and document studies. The research also highlights data security issues, which are critical in managing cloud-based digital archives. The findings reveal that using Google Spreadsheet offers several benefits in archive management, such as improving accessibility, speeding up recording processes, and reducing paper usage. However, some challenges were identified, including limited staff understanding of digital tools and potential data security risks. Based on these findings, the study recommends the development of formal Standard Operating Procedures (SOPs) and regular training for staff to ensure more effective and secure digital archive management. The study concludes that Google Spreadsheet is an effective tool for supporting the digital transformation of archive management, provided it is accompanied by appropriate policies and training. The novelty of this research lies in the development of a model for utilizing Google Spreadsheet as an integrated digital archive management platform with a focus on data security in a government office context. This research contributes significantly to formulating strategies for efficient and secure digital archive management in cloud-based work environments